Contemporary Challenges and Opportunities for Islamic Education in Papua: Al-Qur'an and Hadith Perspectives - Mustahid Mustahid; Surahman Amin; Chairul Anwar Saputra; Nirwan Nirwan; Nurfitriani Nurfitriani (Yayasan Haiah Nusratul Islam, 2026)
Islamic education in Papua represents a vital component of Indonesia’s multicultural educational landscape, particularly within Muslim minority communities. This qualitative study explores the theological foundations, challenges, and future opportunities for strengthening Islamic education from Qur’anic and Hadith perspectives. Data were collected through observations, semi-structured interviews, and document analysis involving students, educators, religious leaders, Muslim youth, and community representatives from MAN Kota Sorong, Kokoda Muslim communities, mosque youth organizations, Muslim organizations, and the Indonesian Ulema Council in Sorong. The findings reveal that Islamic education is anchored in Qur’anic values of knowledge, morality, moderation, tolerance, and social harmony. However, geographical isolation, limited institutional resources, shortages of qualified educators, and unequal digital access constrain its development. Integrating Islamic theology with Papuan local wisdom, particularly the One Furnace Three Stones philosophy, and digital innovation provides a sustainable model for strengthening inclusive, culturally responsive Islamic education in eastern Indonesia.